Potential Role of Caveolin-1 in Regulating the Function of Endothelial Progenitor Cells from Experimental MODS Model - Tianhang Luo; Jixin Shu; Zhengmao Lu; Ting Han; Guoen Fang; Xuchao Xue (Mediators of Inflammation)
Multiple organ dysfunction syndrome (MODS) remains a great challenge in critical care because of its common occurrence, high cost of care, and high mortality. Vascular endothelial injury is the initiation step in the development of MODS, and EPCs are essential for the process of organ repair. It is unclear whether and how caveolin-1 (Cav-1) in EPCs contributes to the pathogenesis of MODS. The present study is aimed at investigating the potential role of Cav-1 in EPCs during MODS. We established a MODS model in pigs, isolated and characterized EPCs from the MODS model, and tracked Cav-1 expression and various in vitro behaviors of EPCs from the MODS model. Then, we knockdown Cav-1 expression with siRNA or induce Cav-1 expression with proinflammatory factors to evaluate potential effects on EPCs. Our results suggest that Cav-1 expression correlated with EPC functions during MODS and Cav-1 regulates the function of endothelial progenitor cells via PI3K/Akt/eNOS signaling during MODS. Thus, Cav-1 in EPCs could be an attractive target for the treatment of MODS.